2013
DOI: 10.1007/s00424-013-1411-0
|View full text |Cite
|
Sign up to set email alerts
|

5,6-EET potently inhibits T-type calcium channels: implication in the regulation of the vascular tone

Abstract: T-type calcium channels (T-channels) are important actors in neuronal pacemaking, in heart rhythm, and in the control of the vascular tone. T-channels are regulated by several endogenous lipids including the primary eicosanoid arachidonic acid (AA), which display an important role in vasodilation via its metabolism leading to prostanoids, leukotrienes, and epoxyeicosatrienoic acids (EETs). However, the effects of these latter molecules on T-currents have not been investigated. Here, we describe the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…12 However, Ca v 3.2 VGCC may play a complex role since it is implicated in vascular relaxation in the coronary artery 21 or it can antagonize relaxation elicited by 5,6-EETs (epoxyeicosatrienoic acids). 37 While the role of L-VGCC in IPA contraction has been extensively described, 38 concentrations used in the present experiments are far greater and this does not allow to discriminate between the respective involvement of Ca v 3.1 and Ca v 3.2 isotypes in the contraction. NNC550396 is a less selective inhibitor of T-VGCC since it inhibits T-and L-VGCC as previously described .…”
Section: Discussionmentioning
confidence: 90%
“…12 However, Ca v 3.2 VGCC may play a complex role since it is implicated in vascular relaxation in the coronary artery 21 or it can antagonize relaxation elicited by 5,6-EETs (epoxyeicosatrienoic acids). 37 While the role of L-VGCC in IPA contraction has been extensively described, 38 concentrations used in the present experiments are far greater and this does not allow to discriminate between the respective involvement of Ca v 3.1 and Ca v 3.2 isotypes in the contraction. NNC550396 is a less selective inhibitor of T-VGCC since it inhibits T-and L-VGCC as previously described .…”
Section: Discussionmentioning
confidence: 90%
“…The actions of the EETs are perhaps the best studied because these epoxides are reported to modulate cardiac function via cardiac L-type Ca 2+ currents (Xiao et al, 2004), K ATP currents , and even T-type Ca 2+ currents (Cazade et al, 2013)-observations that fit well with the smaller QT prolongation and the less marked ST elevation in isolated murine hearts after perfusion with 14,15-EET . Like many other actions of the EETs, the positive effects on cardiac myocytes reportedly relied on the activation of PKA.…”
Section: B Cytochrome P450-derived Mediators In the Heartmentioning
confidence: 93%
“…The heart’s electrophysiology is governed by various ion channels. While there is an abundance of studies demonstrating the effect of EETs on several ion channels in the heart, fewer studies have demonstrated specifically that CYP2J2 levels can affect cardiac electrophysiology [ 95 , 96 , 97 , 98 , 99 , 100 ]. One study by Lu et al found that when CYP2J2 is overexpressed in transgenic mouse hearts, basal K ATP currents were almost two-fold greater when compared with wild-type mice [ 101 ].…”
Section: Cyp2j2 and Cvdmentioning
confidence: 99%